2019
DOI: 10.38150/sajeb.8(3).p91-102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bee pollen extract on lead-induced toxicity in rat testis

Abstract: <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:-536870145 1107305727 0 0 415 0;} @font-face {font-family:"Calibri Light"; panose-1:2 15 3 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 415 0;} @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The results of the present study are in line with the results of the above studies. In another study, Bouazza et al (2018) stated that lead acetate created empty spaces between germ cells. Aftab and Abdul Rauf, (2014) attributed the vacancy between the germ cells to the Sertoli cell damage, which is caused by genotoxic and antiproliferative effects of compounds such as lead acetate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study are in line with the results of the above studies. In another study, Bouazza et al (2018) stated that lead acetate created empty spaces between germ cells. Aftab and Abdul Rauf, (2014) attributed the vacancy between the germ cells to the Sertoli cell damage, which is caused by genotoxic and antiproliferative effects of compounds such as lead acetate.…”
Section: Discussionmentioning
confidence: 99%
“…BaSalamah et al (2018) in their study reported atrophy of the seminiferous tubules and destruction of germ cells and sertoli cells in the testis while exposed to rat lead acetate. In another study, Bouazza et al (2018) stated that lead acetate reduced the height of the germ epithelium and created empty spaces between the germ cells. Dorostghoal et al (2011) also reported a significant dose-dependent decrease in the height of the germinal epithelium during the neonatal, pre-pubertal, and post-pubertal periods of rats exposed to lead acetate.…”
Section: Groupsmentioning
confidence: 99%
“…3,4 Many studies revealed that lead acetate could cause infertility in male. 5 A study revealed that giving 0.1% lead acetate to rats had reduced testis weight, seminiferous tubulous diameter, epididymal sperm count, and serum testosterone level. 6 study revealed that 20 mg/kg BW lead acetate could caused the decrease of testis weight and diameter of tubulous seminiferous in male mice testis.…”
Section: Introductionmentioning
confidence: 99%